GBIF Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2016)
A dataset containing 114357 species occurrences available in GBIF matching the query: DatasetKey: Data on moths from automatically operating light traps in Denmark. The dataset includes 114357 records from 1 constituent datasets: 110388 records from Data on moths from automatically operating light traps in Denmark. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences